2010
DOI: 10.1007/s13219-010-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

Pourquoi fouiller des dépôts funéraires pillés ? Deux exemples et quelques réponses de Keushu (Ancash, Pérou)

Abstract: Looted tombs at Andean archaeological sites are largely the result of a long tradition of trade in archaeological artefacts, coupled to the 17 th century policy of eradicating ancestor veneration and destroying mortuary evidence in a bid to "extirpate idolatry." On the surface, looted funerary contexts often present abundant disarticulated and displaced human remains as well as an apparent absence of mortuary accoutrements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Comparison with radiocarbon dates from Palpa (Unkel et al 2012) shows that the dating of the ceramic chronology holds true across the south coast area. This research also importantly shows that looted remains can be placed within a proper chronological framework, despite the disturbed contexts from which they come (Isla and Reindel 2008;Gerdau-Radonic and Herrera 2010) and thus these remains can be used as a source of direct evidence, e.g., stable isotope analyses of human remains about ancient diet, mobility, and social distinctions (Cadwallader 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Comparison with radiocarbon dates from Palpa (Unkel et al 2012) shows that the dating of the ceramic chronology holds true across the south coast area. This research also importantly shows that looted remains can be placed within a proper chronological framework, despite the disturbed contexts from which they come (Isla and Reindel 2008;Gerdau-Radonic and Herrera 2010) and thus these remains can be used as a source of direct evidence, e.g., stable isotope analyses of human remains about ancient diet, mobility, and social distinctions (Cadwallader 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Although in 1882 Peru was one of the first countries of the American continent to approve and adopt a legislation for the protection of cultural heritage, it was -and still is today -among the countries most affected by devastation of archaeological sites and landscapes (Batievsky & Velarde 2006). In the past, the phenomenon of the huaqueo -archaeological looting -was deeply based on a close relationship between huaqueros -who dug clandestinely for earning a living -and those who managed a rich and well-organized business with the connivance of museums, auction houses, and private collectors (Alva 2001;Gerdau-Radonic & Herrera 2010).…”
Section: Introduction and Research Motivation 11 Premisementioning
confidence: 99%
“…This lack of scholarship stems in part from the belief that disturbed and fragmentary remains have lost most of their scientific value and that the fragmentary and isolated nature of the remains renders the establishment of differential diagnoses or demographic comparisons too challenging (Gerdau-Radonic and Herrera 2010; Toyne, Murphy, and Klaus 2020). While recent bioarchaeological studies of looted Prehispanic communal tombs have demonstrated that valuable data can be extracted from those commingled contexts (Bongers 2019;Gerdau-Radonic and Herrera 2010;Lane, Pomeroy, and Davila 2018;Velasco 2014Velasco , 2018, very few of them have focused exclusively on paleopathology (see Lowman, Harrod, and Turner 2018;McCool, Anderson, and Kennett 2021a;Nelson et al 2020;Titelbaum 2020;Titelbaum, Ibarra, and Naji 2015;Titelbaum, Ibarra, and McNeil 2019;Titelbaum et al 2021).…”
mentioning
confidence: 99%